DIAMOND LIKE CARBON (DLC) COATING ON CARBON STEEL WITH PLASMA TECHNIQUES FOR GAS PIPES - Yahya, Ilham Nur Dimas; Rudyardj, Djony Izak; Ady, Jan (Universitas Airlangga, 2020)
A study about coating on carbon steel by plasma technique aims to determine the variation of time and pressure on the hardness and corrosion strength of a material. The material used in this research was carbon steel with carbon chest of 0.245%. This carbon steel was a plasma technique process with a temperature of 300oC and various pressure variations, such as 1.2 mbar; 1.4 mbar; 1.6 mbar; 1.8 mbar; And 2.0 mbar. The highest hardness was found at 1.8 mbar pressure, which was 161.7 VHN. Then set with a temperature of 300oC and a pressure of 1.8 mbar and a time variation, which were 1 hour; 1.5 hours; 2 hours; 2.5 hours; 3 hours. The largest hardness value was obtained at 3 hours with a hardness value of 161.7 VHN. Then the corrosion test obtained the optimum value at 2 hours with a corrosion value of 0.69 mpy. This was because on the surface of carbon steel there was a layer of Diamond Like Carbon (DLC).